«PHILOSOPHICAL PERIPETIAS» 1965-2015: RETROSPECTIVE OF CONTENT - «Філософських перипетій», Редакція (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2016)
Journal of Kharkov University. The series "Philosophy" / [ed. be Y. F. Bukhalov]. - Kharkiv: Kharkiv University Press, 1965. – № 6. – Issue 1. Journal of Kharkov University. The series "Philosophy" / [ed. be Y. F. Bukhalov]. - Kharkiv: Kharkiv University Press, 1965. – № 10. – Issue 2.